2021
DOI: 10.3389/fpls.2021.728652
|View full text |Cite
|
Sign up to set email alerts
|

First Sprayable Double-Stranded RNA-Based Biopesticide Product Targets Proteasome Subunit Beta Type-5 in Colorado Potato Beetle (Leptinotarsa decemlineata)

Abstract: Colorado potato beetle (CPB, Leptinotarsa decemlineata) is a major pest of potato and other solanaceous vegetables in the Northern Hemisphere. The insect feeds on leaves and can completely defoliate crops. Because of the repeated use of single insecticide classes without rotating active ingredients, many chemicals are no longer effective in controlling CPB. Ledprona is a sprayable double-stranded RNA biopesticide with a new mode of action that triggers the RNA interference pathway. Laboratory assays with secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 38 publications
0
76
0
5
Order By: Relevance
“…Ledprona is a newly developed sprayable dsRNA-based insecticide active ingredient (ai) that targets synthesis of the proteasome subunit beta 5 (dsPSMB5). 20 As such, it impedes the removal of damaged proteins and may lead to the accumulation of polyubiquitinated protein in cells. Target gene and ledprona sequences are described in U.S. Patent No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ledprona is a newly developed sprayable dsRNA-based insecticide active ingredient (ai) that targets synthesis of the proteasome subunit beta 5 (dsPSMB5). 20 As such, it impedes the removal of damaged proteins and may lead to the accumulation of polyubiquitinated protein in cells. Target gene and ledprona sequences are described in U.S. Patent No.…”
Section: Introductionmentioning
confidence: 99%
“…Target gene and ledprona sequences are described in U.S. Patent No. 11142768 and by Rodrigues et al 20 and are publicly available. In preliminary laboratory and greenhouse trials, ledprona showed good potential for controlling Colorado potato beetles.…”
Section: Introductionmentioning
confidence: 99%
“…System configuration and program settings were performed according to the reagent instructions. β-actin was used as an internal reference gene ( Rodrígues et al, 2010 ). Each experimental unit contains four biological replicates and three technical replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the successful systemic RNAi has been established as an important tool for the development of potential insecticidal dsRNAs that can target essential genes in many other tissues of the insect pests ( Huvenne and Smagghe, 2010 ). More recently, the use of the sprayable double-strand RNA-based biopesticide technology was proven to be effective strategy for controlling Colorado potato beetle Leptinotarsa decemlineata by GreenLight Biosciences ( Rodrigues et al, 2021 ). Not all insects, viz., Lepidopteran and Hemipteran orders, however, show sensitivity to RNAi ( Terenius et al, 2011 ) compared to the Coleopteran order ( Wang et al, 2013 ; Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These advances are bridging the gap between laboratory validation, field trials, and consumer availability and facilitating the integration of RNAi into pest management practices. While more research is needed to fully understand the complex interactions of dsRNAs in the environment, recent advances in the agricultural industry have moved RNAi from the laboratory to the field [ 30 , 31 , 32 ]. dsRNAs have been shown to induce the significant mortality of herbivorous crop pests [ 33 ] and regulate populations through reduced fecundity via phenotype alteration [ 27 ].…”
Section: Introductionmentioning
confidence: 99%